Desenvolvimento de competências ético-morais e o sofrimento moral na formação em enfermagem - Heloiza Maria Siqueira Rennó (2015)
This multiple case study of qualitative approach aimed to analyze the developing process ofethical and moral skills and its relation to the moral suffering of students during nursingformation, especially during curricular internship. The starting point was the assumption thatconfronting the moral issues can lead the student to developing ethical-moral skills and/orcause moral suffering. The basis of the theoretical framework of this research is divided intoBerger, Luckmann and Dubar conceptions on approaching the construction of professionalsocialization. Curtain and Jameton approaches were conducted to locate and analyze the issueof the development of ethical-moral skills and moral suffering, respectively. The fields ofstudy consisted of two higher education federal institutions, with the participation of 58nursing graduate students, during their curricular internship. Data were collected by means ofdocumentary analysis and focus groups. For data analysis, we used content analysis and thefeatures from ATLAS.ti 7.0 software. The study was reviewed and approved by the ResearchEthics Committee in Human Beings with Opinion 648 399. The results showed 2 categories:"moral suffering and moral issues faced in nursing training process" and "Differentperceptions in relation to the ethical-moral skills in nursing education." With these results, itwas possible to develop a conceptual framework on the process of developing ethical andmoral skills in nursing education, as well as its relation to the student's moral suffering andthe representation of a triad of student moral suffering. During the nursing training process,the student can develop the ethical and moral skills and/or experience moral distress ordifferent feelings, with consequent illness, school dropout and reduced professionalresistance. The training nursing process should encourage the development of ethical andmoral skills, avoiding the trigger of moral suffering by means of an ethos that promotesdialogue within the reality of health work process, considering care as an ethical reference.